2018
DOI: 10.1103/physreve.97.062218
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency discrete breathers in long-range systems without on-site potential

Abstract: A mechanism of long-range couplings is proposed to realize low-frequency discrete breathers without on-site potentials. The realization of such discrete breathers requires a gap below the band of linear eigenfrequencies. Under the periodic boundary condition of a one-dimensional lattice and the limit of large population, we show theoretically that the long-range couplings universally open the gap below the band irrespective of the coupling functions, while the short-range couplings cannot. The existence of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In addition to our observations in the present paper, our work paves the way towards further studies to explore the nuances of long-range interactions in nonlinear lattice systems. Examples include bistability of solitary waves [32,33], solitary waves with nontrivial phases [31], and low-frequency breathers [35]. These avenues go beyond the confines of mechanical or magnetic systems and are of broad appeal for a variety of long-range phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our observations in the present paper, our work paves the way towards further studies to explore the nuances of long-range interactions in nonlinear lattice systems. Examples include bistability of solitary waves [32,33], solitary waves with nontrivial phases [31], and low-frequency breathers [35]. These avenues go beyond the confines of mechanical or magnetic systems and are of broad appeal for a variety of long-range phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of new studies continue to elucidate fascinating consequences of long-range interactions. For example, recent studies have revealed the emergence of traveling discrete breathers without tails in nonlinear lattices with suitable long-range interactions [34] and the emergence of a linear spectral gap, which enables the emergence of a low-frequency breather [35], in nonlinear lattices with other long-range interactions. Although there are many theoretical and computational studies of lattice systems with long-range interactions, we are not aware of any experimental realizations of breathers in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work, in fact, brings up the possibility that relevant solutions may fail to exist at higher orders in some important case examples [89]. Studying also long-range interactions may bring about surprises and produce gaps in the spectrum where novel DBs may exist, as per the recent work of [90]. Again, this is a topic meriting further exploration.…”
Section: Outlook and Future Directionsmentioning
confidence: 97%